2002
DOI: 10.1002/ccd.10349
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve correlates left ventricular diastolic dysfunction in patients with dilated cardiomyopathy

Abstract: The relationship between altered coronary circulation and left ventricular (LV) function in dilated cardiomyopathy (DCM) remains unclear. We used the Doppler guidewire and transthoracic echo Doppler in 24 DCM patients to investigate the relationship between coronary flow reserve (CFR) and LV systolic/diastolic function, trying to predict diastolic dysfunction and evaluate DCM severity with CFR. CFR correlated better with the deceleration time (DT) of the E-wave and the ratio of E-wave peak value to that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(50 reference statements)
5
9
0
Order By: Relevance
“…This result agrees with data from Weissmuller et al [20], who found no correlation between rate-pressure product and MBF at rest in patients with heart failure. Left ventricular enddiastolic pressure has been associated with myocardial flow reserve in other studies that examined their relation [22,24,25]. Our study showed no correlation between MBF at rest and left ventricular end-diastolic pressure, but there was significant negative correlation between MBF during hyperemia and left ventricular end-diastolic pressure.…”
Section: Discussionsupporting
confidence: 40%
“…This result agrees with data from Weissmuller et al [20], who found no correlation between rate-pressure product and MBF at rest in patients with heart failure. Left ventricular enddiastolic pressure has been associated with myocardial flow reserve in other studies that examined their relation [22,24,25]. Our study showed no correlation between MBF at rest and left ventricular end-diastolic pressure, but there was significant negative correlation between MBF during hyperemia and left ventricular end-diastolic pressure.…”
Section: Discussionsupporting
confidence: 40%
“…CFR has been demonstrated as a sensitive marker for patient outcome, with echocardiographic studies demonstrating that preserved CFR in the right coronary artery (RCA) predict a favourable patient outcome [74], whereas an impaired or reduced CFR is a predictor of dysfunction and worse patient outcome [74,75]. Although little work has been completed to look at the effect of CFR on the RV function, studies have demonstrated links between impaired CFR and LV diastolic dysfunction [76][77][78]. Galderisi et al [79] demonstrated that decreased CFR is associated with impaired relaxation and increased filling pressures; thus, reduced CFR is independent of LV geometry and preload.…”
Section: Coronary Flow Reservementioning
confidence: 99%
“…Various methods have been used to measure coronary flow in these patients, including coronary sinus thermodilution (3,6), intracoronary Doppler flow wire (7)(8)(9), position emission tomography (PET) (10,11), and transesophageal echocardiography (12). In all these studies, it has been demonstrated that coronary flow reserve is reduced in DCM patients.…”
Section: Introductionmentioning
confidence: 99%